Cooling and recovery from intense exercise - A systematic review of studies with trained athletes - Poppendieck, W.; Faude, O.; Wegmann, M.; Meyer, T. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Cooling after exercise has been suggested as a method to improve recovery during intensive training periods or competitions lasting several days to weeks. It has been investigated in various studies and has also found its way into practice. However, many existing studies include untrained subjects to induce a higher degree of muscle soreness and fatigue due to a reduced fitness level. It is not clear if the results of those studies can be transferred to trained athletes. Although recent review articles on the topic of cooling and recovery exist, none of those has focused especially on trained athletes [Halson, 2011; Leeder et al., 2011]. The purpose of this work was to fill this gap. Methods: A literature search was conducted using the following databases: PubMed, ISI Web of Science, AMED and EMBASE. Inclusion criteria were: a) explicit analysis of trained subjects, b) cooling after exercise, c) performance measurement, d) existence of a control group or condition, e) performance evaluation at least 2 h after cooling to exclude potential precooling effects. In total, 14 studies with 153 subjects were located and analyzed. For all studies, the effect of cooling on performance was determined, and effect sizes (Hedges` g) were calculated. Results: In order to determine under which circumstances cooling may be most beneficial, several parameters of the study design were more closely examined. Regarding performance measurement, the best effects were found for endurance parameters (3 studies/30 subjects, 3.7%, g=0.35), while for jump (3/35, 3.4%, g=0.13), strength (10/113, 2.4%, g=0.12) and sprint performance (4/46, 2.7%, g=0.10), effects were smaller. The effects were most pronounced when performance was evaluated 48 h after exercise (7/71, 5.0%, g=0.34). With respect to the exercise which was used to induce fatigue, effects after strength training (4/39, 3.6%, g=0.18) were slightly larger than after endurance-type exercise (10/114, 2.2%, g=0.16). Cold water immersion (10/117, 2.9%, g=0.19) and cryogenic chambers (2/18, 3.8%, g=0.14) seemed to be more beneficial than cooling packs (2/18, 0.3%, g=0.00). Discussion: Overall, the effects of cooling on recovery were rather small (2.8%, g=0.17). Under appropriate conditions, however, cooling after exercise may have relevant positive effects on performance recovery of trained athletes. Especially for the recovery of endurance performance, relevant beneficial changes were reported.